COMPARATIVE STUDY OF THIN-LAYER CHROMATOGRAPHY BIOAUTOGRAPHY AND ANTIOXIDANT ACTIVITIES OF DIFFERENT PARTS OF CLITORIA TERNATEA (FABACEAE) - PAL, ARNA; CHAKRABORTY, SUDIPTA; BALA, N. N. (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study aims at the investigation of antioxidant activities both by qualitative (thin-layer chromatography [TLC] bioautography) and quantitative (in vitro) methods and thereby comparison of the same in different parts of the plants of Clitoria ternatea (Fabaceae). Methods: Leaves, stems, and seeds were macerated with methanol separately and preliminary phytochemical screening was carried out. The extracts were developed using two mobile phase combinations such as Toluene: Ethyl acetate: Formic acid (5:4:0.2) for test 1 and toluene: Ethyl acetate: Methanol (5:3:2) for test 2 on silica gel GF254 TLC plates and further sprayed with DPPH. Antioxidant and free radical scavenging activities were assayed by inhibition of lipid peroxidation and DPPH method with the different concentrations of test extracts (25, 50, 100, 150 and 200 μg/ml) and standard ascorbic acid. Results: The methanolic extract of the leaves, stems, and seeds revealed to possess chiefly alkaloids, phenols, and flavonoids and have shown promising antioxidant activity by all the methods in dose-dependent manner. Leaves were found to be most potent having IC50 value of 111.652 µg/ml and 106.683 µg/ml which is almost similar to the stems (IC50 of 111.685 µg/ml and 106.26 µg/ml), respectively, in DPPH method and inhibition of lipid peroxidation. Seeds failed to produce any significant activity in any of the methods performed. Conclusion: The methanolic extract of leaves and stems can act as a potential antioxidant and antiradical, which are highly comparable with standard.